Characterization of Thin MAPb(I1–xBrx)3 Alloy Halide Perovskite Films Prepared by Sequential Physical Vapor Deposition - Juvet Nche Fru; Nolwazi Nombona; Mmantsae Diale (Frontiers in Energy Research, 2021)
Lead iodide (PbI2)-rich methylammonium lead bromide-iodide (MAPb(I1–xBrx)3) thin-films were prepared by sequential physical vapor deposition of methylammonium lead tri-bromide (MAPbBr3) on methylammonium lead tri-iodide (MAPbI3) bottom layer. The structural, optical, morphological, and electrical properties of the thin-films were studied as the thickness of methylammonium bromide (MABr) was increased from 300 to 500 nm. X-ray diffractograms confirmed transformation of tetragonal MAPbI3(x is 0.0) to the cubic-like structure of MAPbBr3 (x is 1.0) as MAPb(I1–xBrx)3 (x = 0.89–0.95) and PbI2 were formed. The bromine mole ratio x decreased as MABr thickness increased. UV-Vis absorption spectra showed that the bandgap of the thin alloy film decreased from 2.21 to 2.14 eV as x decreased. Scanning electron micrographs depicted densely packed grains that entirely covered the substrate and contained very few pinholes. The average grain size increased from 150 to 320 nm as x decreased. Electrical properties showed high charge carrier mobility that increased linearly with MABr thickness. FTO/MAPb(I1–xBrx)3/Au devices using fluorine-doped tin oxide (FTO) as substrate and gold (Au) as contacts were fabricated and current-voltage characteristics were determined. Space-charge-limited current theory was applied to charge carrier mobility and trap density of MAPb(I1–xBrx)3 thin-films. The charge carrier mobility increased as x decreased. The power conversion efficiency (PCE) of FTO/MAPbBr3/Au, FTO/MAPb(I0.11Br0.89)3/Au and FTO/MAPbI3/Au solar cells were 0.56, 0.62, and 1.15%. Devices including titanium dioxide compact layer (c-TiO2) and titanium dioxide mesoporous (m-TiO2) layer as electron transport layers were also fabricated for the application of Mott-Shottky (M-S) theory. Analyses of dark current-voltage and capacitance-voltage curves of FTO/c-TiO2/m-TiO2/MAPb(I0.11Br0.89)3 solar cells revealed a sizeable built-in voltage (Vbi) of 1.6 V and an accumulation of charge at interfaces for voltages greater than 0.2 V, respectively. Similar analyses for FTO/TiO2/MAPbI3/Au showed a small Vbi of 0.7 V and no charge carrier at interfaces. The work paves a way for reproducible growth of MAPb(I1–xBrx)3 for solar cells and sheds more light on the degree of ion migration in mixed halide and pure halide perovskites.